Effect of the External Physical Vibration Lithecbole on the Discharge of Upper Urinary Stones: A Systematic Review and Meta-analysis - Xu, Zi-hao; Zhou, Shuang; Lv, Jian-lin; Wang, Hao (Urology Journal, 2021)
Purpose: The external physical vibration lithecbole (EPVL) is a new device that accelerates the discharge of urinary stones by changing the patient’s body position and providing multi-directional simple harmonic waves. It is clinically employed to improve the stone-free rate (SFR). However, it is not widely accepted in clinical practice due to the lack of high-level evidentiary support and a standard protocol. The present meta-analysis aims at the evaluation of the efficacy and safety of EPVL treatment in improving the SFR. Methods: This study was a systematic review and meta-analysis. A systematic literature review was conducted using PubMed, Scopus, Embase, Medline, the Web of Science, and the Cochrane Library to find randomized controlled trials (RCTs) as recent as April 2020 that evaluated the efficacy and safety of EPVL treatment for patients with stones/residual stones in the upper urinary tract. Results: In total, 7 prospective studies with 1414 patients were included. Compared with patients in the control group, patients treated with an EPVL (the intervention group) had higher SFRs (95% CI: 0.59-0.86, RR = 0.71, P = .0004) and lower complication rates (95% CI: 1.37-3.12, RR = 2.07, P = .0006). In a subgroup analysis based on previous surgery (ESWL, RIRS), the intervention group had an improved SFR as compared to the control group (95% CI: 0.59-0.95, RR = 0.75, P = .02; 95% CI: 0.56-0.73, RR = 0.64, P < .00001, respectively). In a subgroup analysis based on stone location, the SFRs for stones in the upper/middle/lower calyx and renal pelvis were significantly higher in the intervention group than in the control group: for residual stones in the upper and middle calyx, 95% CI: 0.63-0.98, RR = 0.79, and P = .03; for residual stones in the lower calyx, 95% CI: 0.54-0.75, RR = 0.64, and P < .00001; for residual stones in the renal pelvis, 95% CI: 0.47-0.79, RR = 0.61, and P = .0002. However, the SFRs for ureter stones were not significantly different between groups (95% CI: 0.82 -1.05, RR = 0.93, P = .23). Conclusion: The external physical vibration lithecbole can effectively improve the SFR after ESWL and RIRS without significant side effects, especially for residual stones in the upper/middle/lower calyx and renal pelvis.